From dimictic to monomictic: Empirical evidence of thermal regime transitions in three deep alpine lakes in Austria induced by climate change. (12th May 2017) - Ficker, Harald; Luger, Martin; Gassner, Hubert
Abstract: Duration and timing of thermal stratification and the period of vertical mixing are crucial for internal chemical and biological processes of deep temperate lakes. Climatic changes induced a prolongation of thermal stratification in many lakes over the last decades. This study provides a comparative assessment of observed climate‐induced changes in thermal and limnological properties of three originally dimictic temperate lakes. We analysed 41 years of vertical sampling data of Lake Irrsee (IR), Mondsee (MO) and Hallstätter See (HA) located in the Salzkammergut lake district of Austria. We examined temperatures in surface and bottom waters, quantified changes in thermal regimes and investigated the development of hypoxia,  anoxia and phosphorus concentrations of the three lakes from 1975 to 2015. Mean annual surface‐water temperatures increased substantially, whereas bottom‐water temperatures showed insignificant trends in IR and MO and a slight rising trend in HA. Resulting higher vertical temperature gradients caused stronger thermal stabilities of the lakes. Based on calculations of daily thermal stability, all three lakes showed a significant prolongation of the stratification period with +31 days (±7 days) in IR, +37 days (±7 days) in MO and +28 (±8 days) in HA. We observed greater changes in the timing of onset of stratification compared to the changes in the timing of stratification termination (IR onset −19 days versus termination +11 days, MO onset −21 days versus termination +16 days, HA onset −16 days versus termination +12 days). We found that expanding seasonal hypoxia and anoxia were correlated to prolonged seasonal stratifications and to increasing phosphorus concentrations in bottom‐water layers. However, higher phosphorus concentrations in bottom waters did not raise the lakes′ volume‐weighted total phosphorus concentrations. Under ongoing climate change, alterations in the thermal characteristics will inevitably lead to a transition of mixing regimes from a dimictic to a monomictic mixing pattern in originally ice‐covered temperate lakes. Our investigation revealed that this transition will be earlier in larger and deeper lakes.